Assimilation of Ship-Mounted ADCP Data for Barotropic Tides: Application to the Ross Sea - Erofeeva, S. Y.; Padman, Laurie; Egbert, Gary
The application of a generalized inverse approach for assimilating vessel-mounted acoustic Doppler current profiler (VM-ADCP) data into numerical solutions of barotropic tides is described. The derived estimates of tidal currents can be used to detide the VM-ADCP data and expose underlying mean circulation. The methodology is illustrated with data assimilation models of tidal currents in the Ross Sea. The prior solution, obtained by solving the nonlinear shallow-water equations by time stepping with a linear bottom friction parameterization and elevation of open boundary conditions obtained from a circum-Antarctic tide model, provides reasonably good fit to most available moored current meter data. Two inverse solutions were obtained: one assimilating moored current meter records and the other assimilating three cruises of VM-ADCP data. Fitting either the mooring time series or the VM-ADCP records leads to only small changes relative to the prior solution currents, except over the shelf break where short length scale, energetic diurnal topographic vorticity waves are present. It is shown that the dynamics embedded in the representer functions provides reasonable tidal corrections even with no prior information about forcing at open boundaries.